Islamic heritage architecture and art - Brebbia, C. A.; Boquera, A. Martínez (WIT transactions on the built environment ;, 2016)
Containing papers presented at the first international conference on the topic, this book examines architecture in the Islamic world and the influence it has had in non-Islamic countries.